Cultural Resilience in the Digital Era: A Study on Traditional Music and Urban Adolescents - Rusnalasari , Zulidyana Dwi (Indonesian Scientific Publication, 2025)
Globalization has reshaped cultural consumption among youth, particularly in urban centers where traditional music struggles to maintain relevance. This study investigates how globalization affects adolescents' perceptions and engagement with traditional songs in Makassar, Indonesia. Utilizing a qualitative descriptive approach, the research involved ten youth participants aged 15 to 19 and employed interviews, observations, and documentation. The findings indicate a dominant preference for global music genres such as K pop and Western pop, shaped largely by exposure through platforms like YouTube and TikTok. Traditional songs were minimally recognized and often regarded as outdated. However, youth expressed willingness to re-engage with traditional music if presented through modern digital formats. The study highlights the breakdown of intergenerational cultural transmission and the limited role of schools and families in cultural education. Nonetheless, digital media and participatory culture present viable strategies for revitalizing traditional music. By promoting hybrid musical forms, community based initiatives, and educational reforms, traditional music can be repositioned as a dynamic component of youth identity. The study contributes to cultural sustainability discourse, offering actionable insights for policy and practice in preserving musical heritage in urban, globalized contexts.